Analysis of Local Water Humidity Effect Characteristics Based on Meteorological Data: A Case Study of Nanjing - Kai Liu; Yan Zeng; Xinfa Qiu; Yuheng Zhong (Atmosphere)
In order to explore the variation law and causes of the humidity effect of local water bodies, this paper selects the data of encrypted automatic weather stations (encrypted stations) and national conventional meteorological stations (conventional stations) in Nanjing from 2014 to 2020, and systematically studies the humidity effects and influencing factors of urban water bodies by constructing the humidity effect intensity (E) based on the conventional stations. The results show that the humidity effect of urban water has significant diurnal and monthly variation characteristics, and is extremely sensitive to temperature change, and compared to nighttime, the daytime period is generally more humid. The humidity effect is mostly normal in winter, while the humidification and humidity reduction effects in summer are particularly significant. There are also significant differences in the humidity effect between different typical water stations, which are mainly influenced by the background environment of urban and suburban areas, macro wind field, and local wind field configuration around the water body due to the dense building density in the main urban area, which is characterized by dry humidification, while the suburbs are characterized by humidity. When the water body is located on the side of a large water body (river or lake), the influence of local water–land wind field and macro wind field on the humidity effect is particularly significant, and the water wind will significantly enhance the humidity effect, while the land breeze will weaken the humidity effect. The research results can provide a reference for the urban planning and the design of the surrounding environment of water bodies in Nanjing.